Feasibility of Home‐Based Computerized Working Memory Training With Children and Adolescents With Sickle Cell Disease. Issue 9 (26th May 2016) - Hardy, Steven J.; Hardy, Kristina K.; Schatz, Jeffrey C.; Thompson, Amanda L.; Meier, Emily R.
Abstract : Background: Children with sickle cell disease (SCD) are at increased risk for neurocognitive deficits, yet the literature describing interventions to ameliorate these problems and promote academic achievement is limited. We evaluated the feasibility and preliminary efficacy of a home‐based computerized working memory (WM) training intervention (Cogmed) in children with SCD. Procedure: Youth with SCD between the age of 7 and 16 years completed an initial neuropsychological assessment; those with WM deficits were loaned an iPad on which they accessed Cogmed at home. Participants were instructed to work on Cogmed 5 days each week for 5 weeks (25 training sessions). We examined Cogmed usage characteristics and change on WM assessment scores following the intervention. Results: Of the 21 participants (M age = 11.38, SD = 2.78; Mdn age = 10.00, interquartile range [IQR] = 5.00; 52% female) screened, 60% exhibited WM deficits ( n = 12) and received the intervention and 50% ( n = 6) completed Cogmed. The mean number of sessions completed was 15.83 (SD = 7.73; Mdn = 17.00, IQR = 16.00); females were more likely to complete Cogmed, χ 2 (1) = 6.00, P = 0.01. Participants who reported lower SCD‐related pain impact completed more sessions (r = 0.71, P = 0.01). Children who completed Cogmed exhibited improvements in verbal WM, visuospatial short‐term memory, and visuospatial WM. Conclusions: Initial findings suggest Cogmed is associated with WM improvement in youth with SCD; however, adherence was lower than expected. Home‐based WM interventions may ameliorate SCD‐related WM deficits but strategies are needed to address barriers to program completion.